Current Insights in Cutaneous Lupus Erythematosus Immunopathogenesis - Garelli, Colton J.; Refat, Maggi Ahmed; Nanaware, Padma P.; Ramirez-Ortiz, Zaida G.; Rashighi, Mehdi; Richmond, Jillian M. (Frontiers in Immunology, 2020)
Cutaneous Lupus Erythematosus (CLE) is a clinically diverse group of autoimmune skin diseases with shared histological features of interface dermatitis and autoantibodies deposited at the dermal–epidermal junction. Various genetic and environmental triggers of CLE promote infiltration of T cells, B cells, neutrophils, antigen presenting cells, and NK cells into lesional skin. In this mini-review, we will discuss the clinical features of CLE, insights into CLE immunopathogenesis, and novel treatment approaches.